Kebijakan Redaksi Kompas TV Makassar Dalam Menayangkan Berita - Asrianti, Nur; Herman, Achmad; Akifah, Andi (Universitas Muhammadiyah Jember, 2019)
An editor of electronic media has the authority to determine what news is appropriate to be displayed, and disseminated. Editor of Kompas TV has the right to display and not display a news, there is even news that can air more than once on a different day, there is news that does not show because there is news that aired first and the time is up for the news segment. Kompas TV Makassar also has several terms and conditions in assessing how feasible a news can be displayed so that it can become public consumption. Kompas TV Makassar has never feared the opinions of audiences when they played back the news that had been airedKeywords: Editor, Displaying News, Kompas TV Makassar